Evaluating the use of groupware technologies in support of collaborative learning in an esp tertiary education course - Mavri, Aekaterini; Hadjiconstantinou, Stavroulla (My University, 2018)
ESP (English for specific purposes) refers to English teaching and learning with a strong emphasis on discipline-specific competencies and skills. Collaboration provides key benefits in ESP education, in terms of stronger linguistic gains and better written artefacts. Dedicated learning platforms as well as knowledge management and social networking tools, have become central in supporting collaboration in educational settings, yet sufficient evidence of their in-depth contribution and usability, with regards to ESP, is limited. This study seeks to evaluate the perceived usability of two web-based collaborative learning and productivity platforms: (a) Moodle Elgg and (b) Google Drive, Docs & Hangouts, as well as investigate their distinct pedagogical impact on the students’ perceived learning. Results indicate that the affordances of each tool are accountable for the type and extend of activities performed within them, and - consequently – the respective learning outcomes achieved. Significant differences were recorded between the tools and the outcomes render Google Drive as a more appropriate option than Moodle Elgg for the ESP requirements in this study.
Keywords: Collaborative learning; Groupware; Usability; Courseware; Shared workspaces